2020
DOI: 10.37506/ijfmt.v14i2.2693
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Palatal Rugae in Various Sagittal Skeletal Malocclusions in Kerala Population- A Retrospective Study

Abstract: The present study was designed evaluate the structural morphology of palatal rugae in Kerala orthodontic subjects with varying Sagittal Skeletal Malocclusions. Pretreatment maxillary casts of 105 patients were analyzed for rugae patterns qualitatively and quantitatively using modified Thomas and Kotze classification. The data were statistically analyzed. According to the Fishers exact test, the most common type of rugae pattern in all the groups (Class I, Class II, and Class III) were observed to be wavy follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Studies by Solarte et al , Crystal Runa et al , Heydari et al described horizontal rugae with parallel distribution. [14,[19][20] STUDIES ON SAGITTAL DIMENSION 15 articles had attempted to identify an association between palatal rugae and sagittal malocclusions. One study that compared class II division I with class I rugae pattern was by Gandikota et al [12] STUDIES ON VERTICAL DIMENSION Solarte et al, Sudhakar et al, Maria E. Saadeh et al are three studies which compared the relationship between palatal rugae & vertical dimension.…”
Section: Studies On Direction Of Palatal Rugaementioning
confidence: 99%
See 2 more Smart Citations
“…Studies by Solarte et al , Crystal Runa et al , Heydari et al described horizontal rugae with parallel distribution. [14,[19][20] STUDIES ON SAGITTAL DIMENSION 15 articles had attempted to identify an association between palatal rugae and sagittal malocclusions. One study that compared class II division I with class I rugae pattern was by Gandikota et al [12] STUDIES ON VERTICAL DIMENSION Solarte et al, Sudhakar et al, Maria E. Saadeh et al are three studies which compared the relationship between palatal rugae & vertical dimension.…”
Section: Studies On Direction Of Palatal Rugaementioning
confidence: 99%
“…The orientation of the rugae were found to be directed in the posterior direction in Class II Malocclusion than in others when viewed sagitally. [15,20] The Class II division 2 malocclusion has increased the length of rugae due to environmental factors. [20] There were contradictory results found with regards to the association between sagittal malocclusion and rugae patterns and found no statistically significant difference among different malocclusion about rugae pattern [12,[14][15][20][21] whereas few studies reported that the primary, secondary as well as the fragmentary rugae were greater in class II malocclusion and has significant difference in rugae pattern with class II malocclusion than class I and class III.…”
Section: Sagittal Aspectmentioning
confidence: 99%
See 1 more Smart Citation